Historical review of sexual offence and child sexual abuse legislation in Australia: 1788–2013 - Adam M. Tomison
Abstract: The report provides an overview of the socio-political factors and events that have influenced the development of Australia’s child sexual abuse legislation from 1788-2013. Key developments in relevant legislation during this period which are discussed in detail in the report include: the decriminalisation of homosexual acts between consenting males the removal of gendered language from legislation to enable the law to deal with matters involving male victims, female offenders and same sex offences broadening the definition of sexual intercourse introduction of specific legislation relating to child pornography introduction of mandatory reporting laws